Investigation of Learning Activity In Secondary School - Maison, Maison; Astalini, Astalini; Kurniawan, Dwi Agus; Darmaji, Darmaji; Pratiwi, Nur Ika Sandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to examine the activeness of student learning towards science subjects in junior high school. The research method used was a mixed research method with an explanatory design. The subjects were students of junior high school amounted to 148 students. The analysis of data using statistical techniques descriptive for quantitative data and analysis Miles Huberman for qualitative data. The results of the five indicators show that students are categorized as having good learning activeness on the indicator